“Opting Out of AI”: exploring perceptions, reasons, and concerns behind faculty resistance to generative AI - Shata, Aya (Frontiers in Communication, 2025)
Research on Generative Artificial Intelligence (GAI) in higher education primarily focuses on faculty use and experiences, with limited attention given to why some abstain from using it. Drawing from Innovation Resistance Theory, this study aims to address this gap by exploring the perceptions of both faculty users and non-users of GAI, identifying the reasons and concerns why they avoid GAI. A survey of 294 full-time higher education faculty from two mid-size U.S. public universities was conducted. Using qualitative and quantitative analysis, results show that over one-third of the faculty members opted out of using GAI for five primary reasons: not ready/not now, no perceived value, identity in tension, threat to human intelligence, and future fears and present risks. While both groups expressed concerns about academic dishonesty, non-users associate GAI with broader negative societal consequences, whereas users viewed it as related to innovation and potential benefits. For non-users, top concerns included a perceived lack of originality and accountability, while users were primarily concerned with accuracy. Surprisingly, general comfort with technology emerged as a significant predictor of non-user faculty’s behavioral intention to use GAI. This research contributes to understanding faculty resistance to GAI, emphasizing the need to balance its benefits with drawbacks in higher education.